The Effect of Moringa Leaves Extracts on MDA Level in Male Mice Exposed to Electromagnetic Radiation of Mobile Phones - Nadia Ilmi Amalia; Trianggoro Budisulistyo; Dhega Anindita Wibowo; Tun Paksi Sareharto (Jurnal Kedokteran Diponegoro, 2024)
Background: The use of cell phones causes anxiety about the effects of electromagnetic wave radiation emitted because of the production of free radicals in the body is increased by cell phone electromagnetic wave radiation. This escalation results in an elevated production of Reactive Oxygen Species (ROS), resulting in elevated Malondialdehyde (MDA) levels due to lipid peroxidation, which is toxic to the body. One way to reduce MDA levels is to introduce antioxidants into the body. Previous studies have found that Moringa leaf extract can be used as a good source of antioxidants. Objective: The aim of this research was to assess the impact of Moringa leaf extract administration on the MDA levels in BALB/C mice subjected to electromagnetic waves emitted by cell phones. Methods: This study employed an experimental study with a post-test only control group design. The research involved 23 male BALB/c mice, divided into four groups. The healthy control group received no treatment, while the negative control group was exposed to cell phone electromagnetic waves for 2 hours/day. Groups P1 and P2 received Moringa leaf extract at doses of 100 mg/kgBW and 400 mg/kgBW, respectively, in addition to being exposed to cellular phone electromagnetic waves for 2 hours/day. The treatment was administered for 30 days following a 7-dayadaptation period. On the 31st day, blood plasma samples were takenfrom all mice and examined for MDA levels. The data underwent analysis through non-parametric One-Way ANOVA and subsequent Pos Hoc LSD tests. Significance is acknowledged for p-values less than 0.05. Results: The highest MDA levels were found in the K (-) group, namely 0.43 ± 0.18 ppm, and the lowest MDA levels were observed in the P1 group, with values of 0.19 ± 0.08 ppm. A significant difference was noted between the K (-) group and the P1 group (p = 0.05), while no significant difference were observed in the other groups. Conclusion: Administering Moringa leaf extract at a dose of 100 mg/kgBW/day can reduce MDA levels in mice exposed to electromagnetic waves from cell phones.